THE LONG-TERM RESULTS OF ENDOSURGICAL TREATMENT OF PARESISOPHAGEAL HERNIAS - Makhmud V. Timerbulatiov; Efim I. Senderovich; Elena E. Grishina; Bulat M. Garifullin; Eduard F. Gimaev; Nikita M. Kazakov; Ruslan K. Ibragimov (Креативная хирургия и онкология, 2017)
Introduction. There is a perception that the use of a mesh for surgical treatment of paraesophageal hernias significantly reduces the number of recurrences. But considering the numerous complications associated with mesh reinforcement, there is a need of strong indication for it. It is not still clear what is the best shape of a mesh, the best material and the appropriate way of fixation. Thus, in last years with the accumulation of surgical experience there are a growing number of patients which are not satisfied with the results of operative approach. In this regard, it is important to study the long-term results of treatment and determine causes of failures.Materials and methods. In the clinic of faculty surgery department based in Hospital № 21, Ufa, 22 laparoscopic operations for patients with parasophageal hernia were performed in 2012-2017 (main group). The comparison group consisted of 87 patients operated for sliding hiatal hernia without using a mesh. Long-term results were studied in terms of 6 to 60 months after the operation. Results. 9 (53%) of the patients in the main group and 54 (62%) of the control group had problems with swallowing in the early postoperative period. There was no difference in the incidence of early postoperative dysphagia between the groups (p = 0.1345). In the period from 6 months to 5 years after the operation, 13 (12%) patients complained of dysphagia of varying severity. Comparing the incidence of dysphagia in the main and control groups, a statistically significant difference was found in favor of the control group: 6 patients (27%) versus 6 patients (7%), p = 0.027. Comparing radiological recurrences of the hiatal hernia revealed a significant advantage in favor of the main group: no radiologic relapse versus 5 (6%) in the control group.Conclusion. Laparoscopic surgical treatment of paraesophageal hernias types III and IV with the use of a mesh is an effective and safe method for up to 5 years after surgery, but the technical details of the operation still remain the subject of discussion.